Replacing of soybean meal with sunflower meal with and without multi-enzyme on laying performance and egg quality in Hy-Line laying hens - Marami, M; Nobakht, A; Mehmannavaz, Y; Mazlum, F; Mahdavi, S (Journal of the Hellenic Veterinary Medical Society, 2023)
This experiment was performed to evaluate the effects of replacement of different levels of soybean meal with sunflower meal on laying performance and egg quality parameters in laying hens. In this experiment, 360 laying hens from the age of 47 to 57 weeks, in 9 treatments and 5 replications (8 hens in each replication) were divided into a 3 × 3 factorial arrangement consisting of sunflower meal (0, 30, and 60%) and enzyme additive (0, 100 and 200 g/ton) in a completely randomized design for ten weeks. The results showed that the replacement of soybean meal with sunflower meal and enzyme has significant effects on the performance of laying hens. So that 60% replacement of soybean meal with sunflower meal increased the amount of daily feed intake of laying hens (P<.0.05). The use of 200 gr/ton of multi enzyme in laying hens diet, without having significant effects on other performance parameters, increased the amount of daily feed intake (P<.0.05). Concurrently, there was a non-significant (P>.0.05) trend for egg quality parameters, but weights of egg albumin were affected significantly (P<.0.05) substitution of 60% of sunflower meal in diets increased the amount egg albumin weight. In general, in laying hens, it is possible to replace 60% of soybean meal with sunflower meal without adversely affecting the performance and egg quality. The use of a multi-enzyme only increased the amount of feed intake.